Freud's Converts. - Clifford, Vicki (Karnac Books, 2007)
This work is an exploration of the relationship between psychotherapy and religion. Sigmund Freud and Carl Rogers were chosen for this exposition because both of them were seduced by the high status given to science. Both founders of psychotherapies, they left a legacy which is not that of scientists whom they claimed they were. Both Freud and Rogers had a problematic relationship with religion. This has had a lasting effect on the work and attitudes of their respective followers.